Child abuse development at Special Child Development Institute (LPKA) Banda Aceh and Darussaadah Aceh Social Institution - Puteh, M. Jakfar; Bustamam, Amrullah; Nurainiah, Nurainiah (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
The increase of children as Napza users in Aceh is a new problem for all parents. There are two main problems in this study, namely the pattern of coaching drug-addicted children in LPKA and Darussaadah Aceh Social Institution. This study is about the pattern of special guidance provided for children who abuse drugs in Aceh children's special development institutions and child rehabilitation institutions. This research is a combination of normative and empirical research. The results of this study show that LPKA carries out guidance in general. There is no difference between children assisted by drug cases and those with other cases. Meanwhile, in LRSAMP Darussa'adah social care institution, regular psychological guidance is carried out to rehab children addicted to drugs, like other children in Darussa'adah. The obstacle faced by LPKA-Aceh is the absence of SOP for special guidance for drug abuse from the Ministry of Human Rights. LPKA is not a place for rehabilitation of children of drug abuse, so these children are guided the same as other foster children. In LPKA, children of drug abuse are united with other foster children due to limited space. While the absence of a standard guidebook as a model for rehabilitation of children who abuse drugs is one of LRSAMP's challenges. The organization cannot move forward without referrals from the work area below, a lack of volunteer human resources, and the absence of parents of children who want to rehabilitate their child's self-abuse of drugs.